Substrate Reactivity of Polyphenol Oxidase and Browning Inhibition of Fresh-cut Nam Dok Mai Si-Thong Mangoes by Protein-based Sericin Coating - Chalida Chimvaree; Thanakorn Cumsingnok; Chalermchai Wongs-Aree; Suriyan Supapvanich; Theppanya Charoenrat; Racha Tepsorn; Panida Boonyaritthongchai (My University, 2020)
Recent studies aimed to investigate five phenolic substrates' reactivities in terms of PPO activity compared with browning symptom occurrence, as well as the efficiency of sericin extracted from 'Nam Dok Mai Si-Thong' mango in vitro on polyphenol oxidase (PPO) activity, and the efficiency of sericin coating on browning inhibition of fresh-cut 'Nam Dok Mai Si-Thong' mango during storage. The specificity of PPO activity was determined using various substrates such as caffeic acid, catechol, chlorogenic acid, 4-methylcatechol and pyrogallol. PPO extracted from 'Nam Dok Mai Si-Thong' mango was more actively specific to catechol and 4-methylcatechol than other substrates that revealed a darker browning color on mango pieces. In vitro, sericin inhibited the activity of PPO reacted with catechol and 4-methylcatechol substrate in mango extracts. The efficiency of sericin coating on browning inhibition of fresh-cut mangoes was then investigated. Application of a 2% sericin coating maintained the visual appearance including the L* value, browning index, browning score, and inhibited enzymatic browning incidence by lowering the increases in total phenol and PPO activity compared to the control during storage at 10°C for 4 days. However, sericin seemed to have no influence on phenylalanine ammonia-lyase (PAL) activity. Moreover, sericin coating enhanced the antioxidant activity of fresh-cut mango when compared to the control. In conclusion, we found that sericin coating is an effective option to maintain the visual appearance, and inhibit the enzymatic browning incidence, of fresh-cut 'Nam Dok Mai Si-Thong' mangoes during registered storage.
Keywords: Browning; Sericin; Catechol; Chlorogenic Acid; Catechol oxidase; Postharvest Quality and Shelf Life Management